The soul of the city: a reflection - Firdaus Al-Siddiq Fadzil; Abdul Hadi Harman Shah; Abdul Samad Hadi; Shaharudin Idrus (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
This article presents a small scale research on the definition of the soul of a city as an indicator of liveable city that has undergone rapid and drastic changes in the process of urbanization. When humans begin to inquire various questions in their minds with regards to the characteristics of the surrounding town, the knowledge of city’s soul emerges. Humans observe the conditions of a city as they reflect upon themselves. Such reflection is parallel to the development of human mind which result in patterns of the soul of the city as both object and subject of observations: a metaphor and something that is intriguing yet complex. Patterns of the soul of the city contain life’s motives, values and norms, sustainability, complexity and harmony. The city’s soul physical and social development as well as enhancement is a natural driving force among the people, principles and patterns of places of the city itself. With this driving force, liveability is formed whereby any changes either in form or space was to take place, they (the changes) would not be able to influence existing form and soul. However, the biggest challenge in interpreting the essence of the soul of the city is to decode its abstract nature into its physical form which can be touched, seen while remaining its coherence and sustainability.